METHODOLOGY FOR DEVELOPING ECONOMETRIC MODELS OF INNOVATIVE DEVELOPMENT OF THE TRADE SYSTEM AND EXTERNAL STRATEGIC APPROACHES - Makhmatqulov, Golibjon Kholmuminovich (THE INNOVATION ECONOMY, 2026)
The article is based on the methodology of econometric models of trade services development. In addition, the global trend of growth of the share of trade services in GDP, international econometric studies on the development of trade services are studied, and the differentiation of trade services as areas of innovative development is shown.